Study To Evaluate the Performance of a Point-of-Care Whole-Blood HIV Viral Load Test (SAMBA II HIV-1 Semi-Q Whole Blood) - Brook, Gary (J Clin Microbiol, 2021)
Remote areas of many low and middle income (LMI) countries have poor access to HIV viral load (HIV VL) testing. The SAMBA II (simple amplification-based assay) Semi-Q whole-blood test (Diagnostics for the Real World [DRW], Cambridge, UK) is a point-of-care assay, which uses leucodepletion technology to allow whole-blood testing in remote settings. A total of 1,540 consecutive HIV-positive clinic patients in Cameroon (250), United Kingdom (633), Ukraine (412), and Zimbabwe (245) donated venous blood (all countries) and finger prick blood (all except UK) for testing on SAMBA II. SAMBA II results were compared with simultaneous plasma results on the Abbott RealTime HIV-1 (Abbott Molecular, Des Plaines, IL) viral load assay and interpreted as either <1,000 RNA copies/ml or ≥1,000 RNA copies/ml. For 1,528 venous whole-blood samples tested on SAMBA II, overall percent agreement with the reference test at a cutoff HIV VL of ≥1,000 copies/ml was 96.9% (1,480/1,528; 95% confidence interval [CI], 95.9% to 97.7%), negative percent agreement was 97.7% (1,259/1,289; 95% CI, 96.7% to 98.4%), and positive percent agreement was 92.5% (221/239; 95% CI, 88.4% to 95.5%). For 854 finger prick samples, there was 95.0% (811/854; 95% CI, 93.3% to 96.3%) overall percent agreement, 98.0% (625/638; 95% CI, 96.5% to 98.9%) negative percent agreement, and 86.1% (186/216; 95% CI, 80.8% to 90.4%) positive percent agreement. These rose to 93.5% (82.1% to 98.6%), 97.6% (95.6% to 98.8%), and 95.6% (93.3% to 97.3%) after exclusion of aberrant results from the Ukraine center. These results show a high level of agreement between SAMBA-II and a laboratory-based assay. SAMBA-II has a performance that is suitable to use as a VL point-of-care assay in remote settings.